2011
DOI: 10.1074/jbc.m110.166868
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein 4 (MRP4/ABCC4) Regulates cAMP Cellular Levels and Controls Human Leukemia Cell Proliferation and Differentiation

Abstract: Increased intracellular cAMP concentration plays a well established role in leukemic cell maturation. We previously reported that U937 cells stimulated by H2 receptor agonists, despite a robust increase in cAMP, fail to mature because of rapid H2 receptor desensitization and phosphodiesterase (PDE) activation. Here we show that intracellular cAMP levels not only in U937 cells but also in other acute myeloid leukemia cell lines are also regulated by multidrug resistance-associated proteins (MRPs), particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 42 publications
7
125
0
1
Order By: Relevance
“…MRP4 (ATP-binding cassette sub-family C member 4 [ABCC4]) is a member of the multidrug resistance proteins (MRPs) belonging to the C group of the ATP-binding cassette (ABC) protein superfamily, which functions as an energy-dependent, transmembrane efflux transporter. Compelling evidence supports that cAMP extrusion through MRP4 in several cell types provides a complementary mechanism to the phosphodiesterases (PDEs) as modulators of the intracellular concentration of the second messenger (6)(7)(8)(9)(10). In isolated pancreatic acini, we found that secretin-induced cAMP is extruded by ANF through NPR-C receptors coupled to the PLC/PKC pathway, thus restricting its intracellular accumulation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…MRP4 (ATP-binding cassette sub-family C member 4 [ABCC4]) is a member of the multidrug resistance proteins (MRPs) belonging to the C group of the ATP-binding cassette (ABC) protein superfamily, which functions as an energy-dependent, transmembrane efflux transporter. Compelling evidence supports that cAMP extrusion through MRP4 in several cell types provides a complementary mechanism to the phosphodiesterases (PDEs) as modulators of the intracellular concentration of the second messenger (6)(7)(8)(9)(10). In isolated pancreatic acini, we found that secretin-induced cAMP is extruded by ANF through NPR-C receptors coupled to the PLC/PKC pathway, thus restricting its intracellular accumulation.…”
Section: Introductionmentioning
confidence: 82%
“…Blood samples were rapidly centrifuged, and plasmas were collected in ethanol and stored at -20°C. Samples were dried and the remaining residue was suspended for cAMP determination, assessed by competition of [ 3 H]cAMP for PKA as previously detailed (9,19). Results were expressed as picomoles per milliliter plasma.…”
Section: Measurement Of Campmentioning
confidence: 99%
“…MRP4 inhibition induced the differentiation of leukemic stem cells, which are crucial for leukemia initiation, progression, metastasis, and relapse, and one approach to combatting leukemia is to force the cells into differentiation. Moreover, Copsel et al (2011) reported that MRP4 extrusion is directly involved in the regulation of intracellular cAMP in leukemia cell lines. Pharmacological inhibition or small interfering RNA (siRNA) knockdown of MRP4 led to cell cycle arrest and cell differentiation.…”
Section: The Action Of Mrp4 In Pathophysiological Processesmentioning
confidence: 99%
“…Ethanol was dried and residues were resuspended in 50 mM TrisHCl, pH 7.4, 0.1% BSA, for cAMP determination. cAMP content was determined by competitive radio-binding assay for PKA using [ 3 H]cAMP, as described previously (31). The standard curve was generated using different concentrations of cAMP.…”
Section: Camp Assaymentioning
confidence: 99%